UMPAN BALIK HASIL ASSESSMENT CENTRE UNTUK MENINGKATKAN KETERIKATAN KERJA KARYAWAN - , Farisa Hartinah Wedhalaksmi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Previous research had verified correlation between performance problems and the work engagement. Employeesâ work engagements were influenced by job demands and job resources. This study aim to measure the effectiveness of feedback as one kind of job resources on employee engagement. Feedback based assessment centre report was selected due to the objectivity of the data collection process. Assesors as the company representative were being trained to deliver feedback in order to ensure quality of the feedback delivery. The subjects were supervisors recommended by company to attend assessment centre. This study used experimental design that was untreated control group design with pretestposttest, involving 16 participants which were divided into an experimental group (n=8) and a control group (n=8). Work engagement was measured by 17 item Ulrich Work Engagement Scale (UWES) that had been adapted. Hypothesis was tested by using analysis of covariance (ANCOVA) technique by placing the pretest score as a covariant. The study produced evidence that feedback based assessment centre can increase employee work engagement (F = 82,805, p<0,05). The value of work engagement in the group treated with feedback was higher than the untreated group.